Determination of the optimal sowing time for different cotton varieties under irrigation in the Rostov region - Alexander N. Babichev; Rita Ye. Yurkova; Sergei А. Selitsky (Мелиорация и гидротехника, 2025)
Purpose: to determine the optimal sowing time for irrigated cotton depending on the soil warming temperature in the Rostov Region. Materials and methods. The studies were conducted in 2022–2024 in the Rostov Region. The objects of the study were the following cotton varieties: Phoenix, Favorite, S6465 and PGSSKh 1. Biometric and phenological observations, yield records and statistical data processing were carried out. Results. It was determined that among the cotton varieties, the average lowest germination over three years was noted for the S6465 variety (72 %), and the highest – for the Favorite variety (92 %). The maximum linear growth was noted for the PGSSKh 1 variety: by the ripening phase, 102.4 cm in the variant with seed sowing at a soil temperature of 20 °C. It was found that sowing cotton in soil at favorable temperatures (15 °С and 20 °C) contributed to the formation of a larger leaf area duration of plants from 16.1 to 23.9 thousand sq. m/ha depending on the variety. The highest dry mass by the ripening phase was determined for the variety PGSKH 1 in variant 3 – 10.9 t/ha. The least dry biomass of plants on average over three years by the ripening phase was accumulated for the variety S6465 – 3.9; 5.3 and 5.5 t/ha for the three variants, respectively. The maximum amount of raw cotton was obtained on the Phoenix variety in the control variant when sowing in soil warmed up to 15 °C – 16.2 c/ha, the minimum – on the variety S6465 – from 4.0 to 6.7 c/ha for all variants. Conclusions. Sowing cotton at a soil temperature of 10 °C delayed the crop development during the sowing-ripening period in the agroclimatic conditions of the Rostov region, in comparison with the results of crop growth and development when sowing in soil with optimal temperatures, which affected the yield of various cotton varieties.